MAIZE PRICE TRANSMISSION BETWEEN MAJOR MARKETS IN TELANGANA STATE – AN ECONOMETRIC ANALYSIS - D. SRINIVASA REDDY and A. MEENA, M. MAHESHNATH, R. VIJAYA KUMARI, K. SUHASINI (The Journal of Research, PJTSAU, 2023)
This study tests long-run spatial market integration between price pairs of maize in five major markets viz., Badepally, Siddipet, Nagarkurnool, Warangal and Nizamabad of the Telangana State by adopting important econometric tools like Johansen’s multivariate co integration approach, Augmented Dickey-Fuller (ADF), Granger causality test and Vector Error Correction Model(VECM). The study has confirmed the presence of co integration, implying the six years price association among the markets. Toget the additional evidence as to whether and in which direction price transmission is occurring between the market pairs, Granger causality test has been used, which has confirmed Nizamabad to be the price-determining market. Nizamabad has been found comparatively more efficient as it has depicted most bidirectional causal relations with other markets. The Vector Error-Correction Model (VECM) shown the selected markets of maize are employed to know the speed of adjustments for the prices of maize among selected markets, for short run and long run equilibrium of prices. The results show that Badepally, Nizamabad and Warangal market influence prices in the other two major markets i.e., Siddipet and Nagarkurnool.